SISTEM PENGGAJIAN KARYAWAN DENGAN PROGRAM ASP.NET di Perusahaan PT. QLOM SOLUSI BISNIS - Surya, Maulidina (Program Studi Teknik Informatika Universitas PGRI Ronggolawe, 2024)
In a company the payroll system is very important, to support the smooth payment of employee salaries, therefore a payroll application program is needed to provide convenience in employee payroll. It was concluded that the employee payroll procedure used by PT. QLOM BUSINESS SOLUTIONS are basically not well computerized, so data processing is getting more complicated. With the payroll application program, data input and report preparation requires accuracy, because the incoming data can increase and change at any time. Based on the above, it is necessary to have a payroll application program that is able to process data quickly and accurately, thus facilitating the financial staff in the process of paying employee salaries and can improve employee performance